Dioxin and dioxin-like polychlorinated biphenyls (PCBs) in Scottish farmed salmon (Salmo salar): effects of replacement of dietary marine fish oil with vegetable oils - Bell, J Gordon; McGhee, Fiona; Dick, James R; Tocher, Douglas R (Aquaculture, 2005)
Duplicate groups of Atlantic salmon were fed one of four practical-type diets from first feeding to harvest after 115 weeks. The four diets were low fish oil (16% w/w, LFO), high fish oil (35% w/w, HFO), low vegetable oil (17%, linseed oil/rapeseed oil, 1:1 w/w; LVO) and high vegetable oil (35%, linseed oil/rapeseed oil, 1:1 w/w; HVO). Following sample collection of fish around 2 kg weight all groups were switched to the HFO diet for a further 24 weeks. The dioxin concentration in diets was in order, HFO > LFO > LVO > HVO with values ranging from 0.16-1.4 ng TEQ/kg. The dioxin-like PCB (DL-PCB) concentrations were in the same order with values ranging from 0.62-3.68 ng TEQ/kg. Concentrations of dioxins and DL-PCBs in flesh samples were correlated with feed concentrations although values in flesh were always lower than in feed. Flesh dioxin concentrations ranged from 0.10-0.53 ng TEQ/kg and DL-PCBs from 0.58-1.48 ng TEQ/kg. After 24 weeks feeding a fish oil-containing finishing diet (HFO) the flesh dioxin concentrations ranged from 0.20-0.54 ng TEQ/kg and the DL-PCBs from 0.66-1.07 ng TEQ/kg. Feeding the HVO diet resulted in significant reductions in flesh concentrations of 20:5n-3 (EPA) and 22:6n-3 (DHA) to around 25% of the values in fish fed the HFO diet. However, feeding the HFO finishing diet to all groups for 24 weeks resulted in restoration of flesh EPA and DHA concentrations to 80% of the values in fish fed the HFO diet throughout. This study suggests that salmon cultured on diets based on fish meal and oil (HFO) attain flesh dioxin concentrations that are